Design and Simulation of three Phase three Wire Shunt Active Filter using Instantaneous PQ Theory - Giri, Tilak; Pandey, Ram Prasad; Bhandari, Sabin; Moktan, Sujan; Karki, Lagat (Journal of the Institute of Engineering, 2020)
Due to intensive use of power converters and other non-linear loads, power quality is degrading. The presence of harmonics in the power lines result in greater power losses in distribution, interference problems in communication systems. Non linearity reduces the efficiency and power factor of the system. As the power factor reduces, the reactive power demanded from the supply increases which have no any contribution in energy transfer, so compensation is required. For this, shunt passive filter has been developed but it is bulky and frequency dependent and has many drawbacks. In contrast to passive filter, shunt active filter (SAF) has been developed which is smaller and has wide range of applications. In this paper, shunt active filter based on p-q theory is demonstrated for compensating reactive power and current harmonics. Simulation has been done with and without SAF and results are presented and ended with recommendation and conclusion. An effort is made to reduce the THD of the source current below 5% (specified by IEEE).